التصميم الأمثل للمقاطع البيتونية المسلحة ذات الشكل T باستخدام البرمجة اللاخطية وفق الكود العربي السوري - منصور, نزيه; عمران, جمال; عيسى, لونا (Latakia University Journal -Engineering Sciences Series, 2017)
يتناول هذا البحث تصميم المقاطع البيتونية المسلحة ذات الشكل T وفق الكود العربي السوري وصولاً للمقطع ذو الكلفة الأقل، مع اعتبار كافة متطلبات التصميم. تعتمد الطريقة التقليدية على مجموعة من الفرضيات التصميمية ، فيما تهدف هذه المنهجية للوصول إلى الحل الأمثل مع الأخذ بعين الاعتبار للشروط المقيدة، لذلك فإن استخدامها سيقودنا لتصميم المقطع البيتوني المسلح ذو الكلفة الأدنى.يبين هذا البحث إمكانية صياغة هذه المسألة في نموذج برمجي رياضي لاخطي، وذلك من خلال عدة حالات تم استخدامها لشرح كيفية تطبيق هذه النمذجة ضمن شروط الكود العربي السوري.تم اعتماد الطريقة التقليدية المتبعة في الكود العربي السوري لتصميم المقاطع في هذا البحث, باستخدام طريقة البرمجة اللاخطية المضمنة ببرنامج Lingo14.0 من شركة LINDO Systems Inc. وقد أظهرت مقارنة النتائج التوفير الكبير في كلفة المقطع البيتوني المسلح ذو الشكل T.This research deals with the minimum cost design of reinforced concrete T-beams according to the Syrian code. The aim is to minimize the total cost of the beam while respecting all the design requirements. Traditional method depend on a set of suppositions, in the opposite this methodology aim to reach the optimal solution among a set of constraints with respect the objective function. So that, using this methodology leading to the minimum cost reinforced section design. This research is shown that the problem can be formulated in a nonlinear mathematical programming format. Several cases are used to explain the applicability of the formulation in accordance with the current Syrian code. Traditional method of Syrian code has been used to design sections in this paper, utilizing the nonlinear programming method provided by Lingo14.0 software from LINDO Systems Inc. The comparison of the results shows that important saving can be obtained at the total cost of a reinforced concrete T-beams design.